If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(1 + -3x) + -4x = 2(-7 + -3x) + -8 (1 * -5 + -3x * -5) + -4x = 2(-7 + -3x) + -8 (-5 + 15x) + -4x = 2(-7 + -3x) + -8 Combine like terms: 15x + -4x = 11x -5 + 11x = 2(-7 + -3x) + -8 -5 + 11x = (-7 * 2 + -3x * 2) + -8 -5 + 11x = (-14 + -6x) + -8 Reorder the terms: -5 + 11x = -14 + -8 + -6x Combine like terms: -14 + -8 = -22 -5 + 11x = -22 + -6x Solving -5 + 11x = -22 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -5 + 11x + 6x = -22 + -6x + 6x Combine like terms: 11x + 6x = 17x -5 + 17x = -22 + -6x + 6x Combine like terms: -6x + 6x = 0 -5 + 17x = -22 + 0 -5 + 17x = -22 Add '5' to each side of the equation. -5 + 5 + 17x = -22 + 5 Combine like terms: -5 + 5 = 0 0 + 17x = -22 + 5 17x = -22 + 5 Combine like terms: -22 + 5 = -17 17x = -17 Divide each side by '17'. x = -1 Simplifying x = -1
| 3x^2-90x+525=0 | | -19+x=8 | | -2(2-b)=-8(10-5b) | | 1/2((3x^(2)-7x))=6 | | 7w-6w=6 | | -7(n-7)+7(2-8n)=-n+n | | -4m+7m=15 | | 1/2(3x^2-7x)=6 | | 4g+3w=47.5 | | x-y=(-w) | | 13h-12h=7 | | n-48=7(5n+8)-2 | | Y-2=3/4(x-0) | | (1+2x+9x^2+8x^3)+(9-2x+9x^2-8x^3)= | | -(b-11)-36-11=16 | | 7d-2d=15 | | 4t-2=12 | | -8(10b+9)=16+8b | | 9-x/3=5/13 | | 4u+6u=20 | | Y=2x-1+3 | | (9u-5v+9w)-7(-9u+2v-9w)= | | -8x=4(10-3x) | | 5y-4-3y=6 | | 102/-34 | | z+z=20 | | 5(2.85)+7f=28.70 | | 3(4+x)=-6 | | f(x)=9x^2-54x-19 | | -4x-8+8x=24 | | k+7+7k=12+9k | | 105=15b |